Sustaining development and growth in East Asia - Henckel, Timo.; T&F eBooks (Milton Park, Abingdon, Oxon ; New York N.Y. : Routledge, 2012)
"For several decades, fast-growing East Asia has been the envy of the developing world. Not only has East Asia outperformed all other regions of the world, but it also recovered surprisingly swiftly from the 1997-98 Asian financial crisis and the 2008-09 global financial crisis. Nevertheless, investment in the region remains subdued relative to pre-Asian crisis levels. Are current investment rates too low and, given greater investment, could the region grow even more rapidly? This book brings together a rich array of papers analyzing the determinants of, and impediments to, investment and growth. It discusses a range of issues bearing on investment and development. The chapters cover domestic and international economic, institutional and political factors, including the role of foreign direct investment, and the importance of public infrastructure, fiscal policy and export-oriented growth strategies. Trade and trade policy, in particular, are emphasized, with contributions ranging from an analysis of global production networks in electronics manufacturing, to the effects and implications of economic integration in the Mekong states"--Provided by publisher.
1. Introduction / Timo Henckel -- 2. Outward-looking growth strategies in East Asia : rationale and success / Stephen Schwartz -- 3. Facilitating domestic investment and growth / Ponciano S. Intal, Jr, Alfredo R. Paloyo and Maricar Garde -- 4. Global production networks in electronics and intra-Asian trade / Byron Gangnes and Ari Van Assche -- 5. Dynamic gains of trade and foreign direct investment in East Asia / Shujiro Urata -- 6. Post-crisis investment performance of ASEAN countries : importance of FDI / Shandre M. Thangavelu, Yong Yik Wei and Aekapol Chongvilaivan -- 7. Infrastructure investment in East Asia : learning from crisis / John Cheong-Holdaway, Hongjoo J. Hahm and William Wallace -- 8. Some fiscal priorities for development / Richard Hemming and Greetje Everaert -- 9. The rule of law and governance puzzles in democracies and non-democracies / Philip Keefer -- 10. Political institutional structure and governance quality / Tao Kong -- 11. Integration and transition : Vietnam, Cambodia and Lao PDR / Suiwah Leung -- 12. Conclusion / Timo Henckel.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Economic development -- Asia; Investments -- Asia; Asia -- Economic conditions -- 21st century; Asia -- Commerce; Electronic books